2011
DOI: 10.5194/bg-8-3053-2011
|View full text |Cite
|
Sign up to set email alerts
|

Relative effects of precipitation variability and warming on tallgrass prairie ecosystem function

Abstract: Abstract. Precipitation and temperature drive many aspects of terrestrial ecosystem function. Climate change scenarios predict increasing precipitation variability and temperature, and long term experiments are required to evaluate the ecosystem consequences of interannual climate variation, increased growing season (intra-annual) rainfall variability, and warming. We present results from an experiment applying increased growing season rainfall variability and year round warming in native tallgrass prairie. Du… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

12
139
1
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(155 citation statements)
references
References 56 publications
12
139
1
3
Order By: Relevance
“…The function and composition of the plant communities in grassland ecosystems have been proposed to be sensitive to variability in climatic conditions (Knapp & Smith 2001;Gao & Reynolds 2003). In grassland ecosystems, shifts in timing of precipitation -not in the total quantitycan be important controls of plant productivity Fay et al 2011), soil respiration (Harper et al 2005;Fay et al 2011), as well as function and structure of soil communities (Zeglin et al 2013). As soil moisture and its variability are major controls of the broad scale function and composition of the soil communities on various spatial (Brockett et al 2012) and temporal scales (Zeglin et al 2013), more detailed evaluation of community responses to long-term manipulations are timely.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The function and composition of the plant communities in grassland ecosystems have been proposed to be sensitive to variability in climatic conditions (Knapp & Smith 2001;Gao & Reynolds 2003). In grassland ecosystems, shifts in timing of precipitation -not in the total quantitycan be important controls of plant productivity Fay et al 2011), soil respiration (Harper et al 2005;Fay et al 2011), as well as function and structure of soil communities (Zeglin et al 2013). As soil moisture and its variability are major controls of the broad scale function and composition of the soil communities on various spatial (Brockett et al 2012) and temporal scales (Zeglin et al 2013), more detailed evaluation of community responses to long-term manipulations are timely.…”
Section: Introductionmentioning
confidence: 99%
“…While such changes in the per event volume of rainfall as well as in their frequency have been suggested to lead to rapid alterations in soil processes as well as aboveground community composition Fay et al 2003;Harper et al 2005;Swemmer et al 2007;Fay et al 2011), consequences of such alterations for belowground microbial communities have received comparatively less attention (Chou et al 2008;Zeglin et al 2013). This major gap prohibits our understanding of the soil community responses to changes in soil water that far exceed those witnessed for dominant plants (Huxman et al 2004;Ogle & Reynolds 2004;Schwinning & Sala 2004), tend to be more dynamic, and responsive to pulse events (Austin et al 2004;Ogle & Reynolds 2004;Carbone et al 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Climate projections from general circulation models vary as to whether total precipitation will increase or decrease in different regions over the next century, but most models predict increased variability in rainfall patterns (Cayan et al 2008). Many individual below-and aboveground processes that control water (H 2 O), carbon (C) and nitrogen (N) cycling in terrestrial ecosystems are known to be affected by seasonal rainfall patterns (Knapp et al 2002, Austin et al 2004, Xu and Baldocchi 2004, Nippert et al 2006, Carbone et al 2011, Fay et al 2011, Tiemann and Billings 2011. If soil and plant responses result in the net release of carbon from soils, positive carbon cycle-climate feedback loops may amplify climate change (Heimann and Reichstein 2008).…”
Section: Introductionmentioning
confidence: 99%
“…41 It is important to elucidate the mechanisms underlying the relationships between productivity, plant diversity, and 42 precipitation with ongoing global change (Fay et al 2011;Huxman et al 2004; Knapp et al 2008; Knapp et al 2002; 43 Shen et al 2015; Weltzin et al 2003). That is because changing precipitation regimes and other anthropogenic 44 disturbances likely alter community composition and ecosystem functionality, and consequently affect ecosystem 45 services and human welfare (Carmona et 50 A large number of studies have accepted the term of precipitation-use efficiency (PUE, the ratio of ANPP to 51 precipitation) as a proxy of the sensitivity of productivity response to precipitation, because it has normalized the 52 effect of water availability by placing productivity on a per-unit-of-precipitation basis (Bai et Knapp et al (2002) 60 found that PUE was influenced mostly by community composition and that species complementarity ensured greater 61 and more stable productivity in species rich grasslands.…”
mentioning
confidence: 99%